NIVEL DE CONOCIMIENTO DE HÁBITOS DE HIGIENE EN MADRES CON NIÑOS MENORES DE 4 AÑOS DE LA INSTITUCIÓN EDUCATIVA INICIAL CARLOS SHOWING FERRARI HUÁNUCO – 2016 - Rios Ramirez, Laura (2016)
Objective: To identify the level of awareness of personal hygiene show mothers with children under 4 years of the Educational Institution Carlos Showing Ferrari Huanuco in 2016. Methods: The study was observational, prospective, transversal and descriptive . The sample population consisted of 93 mothers with children under four years are enrolled in the Home School "Carlos Showing Ferrari". Selected by non-probability sampling it was applied instruments for data collection: interview guide and questionnaire sociodemographic knowledge about hygiene, taking into account the ethical aspects. The method that was used was Crombach = 0.930 showing that the instrument has high reliability, in inferential analysis nonparametric test Chi-square was used, relying on the statistical package SPSS 21. Results: It was found that 65, 6% of mothers have a good level of knowledge. On the other hand, in comparison variables: the result was age (P = 0.384), occupation (P = 0.546), origin (P = 0.497) because it obtained a (P> 0.05) it follows that the level of knowledge of hygiene unrelated to the comparison variables, which allows us to accept the null hypothesis. Conclusions: P> 0.05 reject allowing comparison variable, ie there is no difference between the level of knowledge of hygiene according to age, occupation and origin: according to the hypothesis test result was obtained.